تطور العمارة الإسلامية في العصر السلجوقي (Comprehensive Journal of Science, 2025)
-        The Seljuks established a large Islamic state that emerged in the fifth century AH/eleventh century AD, to include Khorasan, Transoxiana, Iran, Iraq, the Levant, and Asia Minor. Rayy in Iran and then Baghdad in Iraq were the headquarters of the Seljuk Sultanate, while Seljuk states arose in Khorasan, Transoxiana (Kerman), the Levant (Seljuks of the Levant), and Asia Minor (Seljuks of Rum), and they were subject to the Seljuk Sultanate in Iran and Iraq.-        The Seljuks supported the Abbasid state in Baghdad and supported its Sunni doctrine, after it was on the verge of collapse between the Shiite Buyid influence in Iran and Iraq, and the Fatimid Fatimid influence in Egypt and the Levant. The Seljuks completely eliminated the Buyid influence and confronted the Fatimid Caliphate.-        The Seljuks paid special attention to the architecture of the cities they conquered in Asia Minor. They built many schools, mosques, funeral homes, and hospitals. Despite the continuous wars they fought with their enemies, they had plenty of time to care for and establish many institutions. They built schools for studying medicine, with hospitals attached to them, and filled the caravan routes with inns and built bridges. They also built palaces, baths, and mosques, which were often accompanied by shrines.-        The planning methods of Seljuk religious buildings varied, and modifications were introduced to them to suit the era of their construction and the climatic, political, economic, religious and local environmental factors, as well as to suit the development of the functions performed by these facilities, which formed the main architectural features of mosques, schools and shrines in these countries. They can be considered a direct reflection of their construction style, and specific construction methods and approaches were followed, each of which suited the conditions of construction of this or that building and the architecture of this or that era. Construction methods and materials sometimes had a clear impact on the design of the facilities, and were linked to the social conditions and factors of the life of society in general.-        The Seljuk state was a powerful Islamic state that controlled a vast area of Central Asia, the Middle East and parts of Europe in the period between (the eleventh century until the thirteenth century AD), and one of the most prominent effects left by the Seljuks was their distinctive architectural style, which had a profound impact on the Islamic countries.-        The mosque and the school were the most important basic facilities in Seljuk architecture. These facilities were used to call for Sunni doctrines, the Seljuk faith. They were also cultural and educational institutions according to architectural engineering. The credit for establishing these schools, known as the Nizamiyya, goes to the minister Nizam al-Mulk, who spent generously on them.
Keywords: architecture, Seljuks, mosques, bimaristans(Hospitals), palaces, shrines, schools.